1977
DOI: 10.1139/m77-174
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of enterotoxigenic Aeromonas from fish

Abstract: This paper reports two different enterotoxigenic classes of the genus Aeromonas isolated from fishes. Strains of A. sobria were isolated from healthy fishes only wheras strains of A. hydrophila were isolated from both healthy and moribund fishes. Aeromonas sobria and hydrophilia strains produced a cytotoxic factor and were highly proteolytic. Seventy-five percent (75%) of the A. sobria strains produced only one type of hemolysis on 5% blood agar, but 92% of the A. hydrophilia produced two types of hemolysis. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(46 citation statements)
references
References 8 publications
1
45
0
Order By: Relevance
“…The described Postmortem lesions were in agreement with the results described by Asaad [5], Aboyadak [12], Huizinga et al [13] and AOAD [14]. The internal lesions appeared on infected fish were attributed to both bacterial invasion and colonization also, to its produced toxins described by Boulanger et al [15]. Twelve from sixteen isolate were grown on R-S media giving small yellow colonies which are characteristic for Aeromonas hydrophila as described by Cipriano [16] and for confirmation PCR identification was performed.…”
Section: Resultssupporting
confidence: 89%
“…The described Postmortem lesions were in agreement with the results described by Asaad [5], Aboyadak [12], Huizinga et al [13] and AOAD [14]. The internal lesions appeared on infected fish were attributed to both bacterial invasion and colonization also, to its produced toxins described by Boulanger et al [15]. Twelve from sixteen isolate were grown on R-S media giving small yellow colonies which are characteristic for Aeromonas hydrophila as described by Cipriano [16] and for confirmation PCR identification was performed.…”
Section: Resultssupporting
confidence: 89%
“…Our findings showed that these variables were not reliable for detection of the enterotoxins of Aeromonas. Although Boulanger, Lallier and Cousineau (1977) reported strains of A . hydrophila to be enterotoxin positive in the suckling-mouse test, Cumberbatch et al (1979) and Dobrescu (1978) did not detect the presence of enterotoxins of A .…”
Section: Discussionmentioning
confidence: 99%
“…Various species of Aeromonas have been associated with cases of gastroenteritis, septicemia and wound, soft tissue, skin and blood infections in humans. In addition, the presence of these bacteria may be fatal in immunocompromised patients [2,4,10,15,17].…”
Section: Introductionmentioning
confidence: 99%